2014
DOI: 10.1101/gad.235515.113
|View full text |Cite
|
Sign up to set email alerts
|

Glioma cancer stem cells secrete Gremlin1 to promote their maintenance within the tumor hierarchy

Abstract: Glioblastomas are the most prevalent and lethal primary brain tumor and are comprised of hierarchies with selfrenewing cancer stem cells (CSCs) at the apex. Like neural stem cells (NSCs), CSCs reside in functional niches that provide essential cues to maintain the cellular hierarchy. Bone morphogenetic proteins (BMPs) instruct NSCs to adopt an astrocyte fate and are proposed as anti-CSC therapies to induce differentiation, but, paradoxically, tumors express high levels of BMPs. Here we demonstrate that the BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
123
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 78 publications
6
123
1
Order By: Relevance
“…Despite the presence of BMP expression in primary GBM tissue, glioma CSCs are highly resistant to the differentiation effects of BMPs in a process that occurs through at least two distinct cell-autonomous mechanisms: the shift to a fetal BMP receptor expression in glioma CSCs through recruitment of the transcriptional repressor EZH2 ) and the secretion of BMP antagonists, specifically Gremlin1, by CSCs to protect against endogenous BMPmediated differentiation (Yan et al 2014). In this manner, CSCs generate differentiated progeny that provide supportive cues to the parental cells (e.g., Notch ligands, interleukin-6 [IL-6], and extracellular matrix) while resisting differentiation signals.…”
Section: Niche Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the presence of BMP expression in primary GBM tissue, glioma CSCs are highly resistant to the differentiation effects of BMPs in a process that occurs through at least two distinct cell-autonomous mechanisms: the shift to a fetal BMP receptor expression in glioma CSCs through recruitment of the transcriptional repressor EZH2 ) and the secretion of BMP antagonists, specifically Gremlin1, by CSCs to protect against endogenous BMPmediated differentiation (Yan et al 2014). In this manner, CSCs generate differentiated progeny that provide supportive cues to the parental cells (e.g., Notch ligands, interleukin-6 [IL-6], and extracellular matrix) while resisting differentiation signals.…”
Section: Niche Factorsmentioning
confidence: 99%
“…In a manner that mimics aberrant differentiation, CSCs co-opt developmental programs to maintain an undifferentiated state, increasing their survival and maintenance. Common pathways activated in CSCs include Notch, BMP, NF-κB, and Wnt signaling (Li et al 2009a;Day et al 2013;Rheinbay et al 2013;Lubanska et al 2014;Yan et al 2014). Collectively, niche factors represent an overriding theme in CSC biology, where stem and progenitor cell features provide selective advantages to maintain tumor growth (Fig.…”
Section: Niche Factorsmentioning
confidence: 99%
“…Karagiannis et al (16) showed that GREM1 promotes the loss of cancer cell differentiation at the cancer invasion front, a mechanism that may facilitate tumor progression. Yan et al (17) reported that Gremlin1-overexpressing cells display increased growth and tumor formation abilities. In our study, the association between GREM1 expression and angiogenesis was examined in tumor tissues using numerical values of microvascular structures (MVD) stained with COL15A1 taking into account the fact that COL15A1 serves as an endothelial marker.…”
Section: Discussionmentioning
confidence: 99%
“…This pro-fibrotic signalling is counteracted by BMP-2 signalling, which in turn is inhibited by increased Gremlin1 expression from PSCs triggered by TGF-β1 and other factors. Thus, increased Gremlin1 is both a driver and marker of fibrosis during chronic pancreatitis cancer stem cell (CSC) pluripotency, which has been implicated in colon cancer and glioma initiation and development [26,27]. Thus, pharmacological targeting of Gremlin1 in this scenario would drive CSCs towards a more differentiated tumour cell type that would be more susceptible to chemotherapy and radiotherapy agents [27].…”
mentioning
confidence: 99%
“…Thus, increased Gremlin1 is both a driver and marker of fibrosis during chronic pancreatitis cancer stem cell (CSC) pluripotency, which has been implicated in colon cancer and glioma initiation and development [26,27]. Thus, pharmacological targeting of Gremlin1 in this scenario would drive CSCs towards a more differentiated tumour cell type that would be more susceptible to chemotherapy and radiotherapy agents [27]. Given that CP progresses to pancreas cancer in approximately 7 % of patients, this suggests that Gremlin1 may have overlapping roles in both fibrosis and cancer.…”
mentioning
confidence: 99%